DINAMIKA PENGARUSUTAMAAN GENDER PADA PENDIDIKAN TINGGI ISLAM - Thohir Yuli Kusmanto (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2017)
Gender equality has not been realized in practical terms in public life. Factors that influence it; socio-cultural, political, economic, religious, and others. State policy to overcome them on gender mainstreaming in the form of Presidential Decree 9 of 2000. Praxis has lasted 14 years, socialization and implementation is mostly done, but it needs evaluation. The reality of interesting research in higher education institutions of Islam, because the discourse and praxis which is still being debated, as well as the strategic position for the development and application of knowledge about gender relations. Interesting problem include; outlook leaders Islamic State University Walisongo on gender mainstreaming, the implementation of gender mainstreaming and its implications in the campus environment. This research is a qualitative descriptive case study with a gender perspective, which identifies the gender gap in multi aspect. The study's findings indicate that the views of leaders there Walisongo UIN integral and partially on gender mainstreaming, Implementation PUG; there is a policy that opens the academic community to gain an important position in the hierarchy structure at UIN Walisongo. Research take gender issues openly and freely. Many women researchers examined a variety of themes, education and training to strengthen the capacity of women, and quantitative mapping of gender. PUG strengthen the struggle gender equality, achieving gender equality and equity at a certain level, Islamic lectures Gender Equality and the proportion of women increased structural served._________________________________________________________Keadilan gender secara praksis belum terwujud dalam kehidupan masyarakat. Faktor yang mempengaruhinya; sosial budaya, politik, ekonomi, agama, dan lain-lainnya. Kebijakan negara untuk mengatasinya diantaranya tentang gender mainstreaming (pengarusutamaan gender), berupa Inpres No.9 Tahun 2000. Praksisnya telah berlangsung 14 tahun, sosialisasi dan implementasi banyak dilakukan, tetapi perlu evaluasi. Realitas tersebut menarik penelitian pada lembaga pendidikan tinggi Islam, karena wacana dan praksis yang masih menjadi perdebatan, serta posisinya strategis bagi pengembangan dan penerapan ilmu pengetahuan tentang relasi berkeadilan gender. Temuan penelitian menunjukkan bahwa pandangan pimpinan UIN Walisongo ada yang integral dan parsial tentang pengarusutamaan gender, Implementasi PUG; ada kebijakan yang terbuka civitas akademika untuk meraih posisi penting dalam struktur hierarkhi di UIN Walisongo. Penelitian mengambil isu gender terbuka dan bebas. Banyak peneliti perempuan meneliti beragam tema, pendidikan dan pelatihan penguatan kapasitas perempuan, dan pemetaan kuantitatif tentang gender. PUG memperkuat perjuangaan kesetaraan dan keadilan gender, tercapainya kesetaraan dan keadilan gender pada tingkatan tertentu, perkuliahan Islam Kesetaraan Gender dan proporsi perempuan menjabat struktural meningkat.